2002
DOI: 10.1128/iai.70.9.5107-5114.2002
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity in a Mouse Model of a Conjugate Vaccine Made with a Synthetic Single Repeating Unit of Type 14 Pneumococcal Polysaccharide Coupled to CRM197

Abstract: Oligosaccharides (OSs) related to the pneumococcal type 14 capsular polysaccharide (Pn14PS) were studied for their ability to inhibit the binding between anti-PS14 antisera and native PS14. A synthetic tetrasaccharide corresponding to the repeating unit of the Pn14PS, a hexasaccharide mimic, and an octasaccharide fragment obtained by Pn14PS depolymerization were good inhibitors. CRM197 conjugates of the tetrasaccharide and an octasaccharide mimic were prepared by using either adipic acid diester or diethyl squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 42 publications
5
62
1
1
Order By: Relevance
“…In many cases, the glycans attached in the conjugate are oligosaccharides prepared by degradation of the original polysaccharide (Anderson et al 1986, Costantino et al 1999. In addition, glycoconjugates can be produced from relatively low molecular weight oligosaccharides related to the repeating polymers (Mawas et al 2002, Benaissa-Trouw et al 2001, Jansen et al 2001, Jansen and Snippe 2004, or the short glycans of LPS O-chain (Gupta et al 1998), or low molecular weight capsular polysaccharides such as those expressed by Staphylococcus aureus (Fattom et al 2004). It has been shown possible to make effective glycoconjugate immunogens from low molecular weight oligosaccharides such as those present on the lipo-oligosaccharides of pathogens such as a Neisseria meningitidis (Mieszala et al 2003).…”
Section: Glycoconjugate Vaccinesmentioning
confidence: 99%
“…In many cases, the glycans attached in the conjugate are oligosaccharides prepared by degradation of the original polysaccharide (Anderson et al 1986, Costantino et al 1999. In addition, glycoconjugates can be produced from relatively low molecular weight oligosaccharides related to the repeating polymers (Mawas et al 2002, Benaissa-Trouw et al 2001, Jansen et al 2001, Jansen and Snippe 2004, or the short glycans of LPS O-chain (Gupta et al 1998), or low molecular weight capsular polysaccharides such as those expressed by Staphylococcus aureus (Fattom et al 2004). It has been shown possible to make effective glycoconjugate immunogens from low molecular weight oligosaccharides such as those present on the lipo-oligosaccharides of pathogens such as a Neisseria meningitidis (Mieszala et al 2003).…”
Section: Glycoconjugate Vaccinesmentioning
confidence: 99%
“…The choice of conjugation methods is restricted by the pH and temperature sensitivities of both vaccine components. The types of chemical linkages between the O-SP and the protein as well as the saccharide chain length and the chain density on the protein were shown to influence the serum antibody responses to both vaccine components [35,36,37,38,39,40]. Here we studied two conjugation methods of O-SP either by their Kdo or their glucosamine residues.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that a synthetic branched tetrasaccharide, corresponding to a single structural repeating unit of Pn14PS conjugated to the cross-reactive material of diptheria toxin (CRM197), was found to induce anti-polysaccharide type 14 antibodies by Mawas, F. et al [74]. We continued to investigate further how small the minimal structure in Pn14PS can be and still produce specific antibodies against native polysaccharide type 14 [73].…”
Section: Identification Of the Minimal Structure Of Oligosaccharide Cmentioning
confidence: 99%
“…Meanwhile we and other groups have been working on improving the immunogenicity of neoglycoconjugates against different S. pneumoniae serotypes in animal models: Di-, tri-, and tetrasaccharides related to polysaccharide type 17F conjugated to keyhole limpet hemocyanin (KLH) protein [69,70] and tri-and tetrasaccharides related to type 23 conjugated to KLH protein [71]; Di-, tri-, and tetrasaccharides related to type 6B conjugated to KLH protein [72]; Di-, tri-, and tetrasaccharide related to type 3 conjugated to the crossreactive material of diphteria toxin (CRM197) protein [60] and most recently overlapping oligosaccharide varying from tri-to dodecasaccharides related to polysaccharide type 14 conjugated to CRM197 protein [73,74].…”
Section: Pneumococcal Synthetic Oligosaccharide-based Vaccinesmentioning
confidence: 99%